Lupinalbin A as the most potent estrogen receptor α- and aryl hydrocarbon receptor agonist in Eriosema laurentii de Wild. (Leguminosae) - Ateba, Sylvin Benjamin (BioMed Central, 2014)
BACKGROUND: Eriosema laurentii De Wild. (Leguminosae) is a plant used in Cameroon against infertility and gynecological or menopausal complaints. In our previous report, a methanol extract of its aerial parts was shown to exhibit estrogenic and aryl hydrocarbon receptor agonistic activities in vitro and to prevent menopausal symptoms in ovariectomized Wistar rats. METHODS: In order to determine the major estrogen receptor α (ERα) agonists in the extract, an activity-guided fractionation was performed using the ERα yeast screen. To check whether the ERα active fractions/compounds also accounted for the aryl hydrocarbon receptor (AhR) agonistic activity of the crude methanol extract, they were further tested on the AhR yeast screen. RESULTS: This study led to the identification of 2′-hydroxygenistein, lupinalbin A and genistein as major estrogenic principles of the extract. 2′-hydroxygenistein and lupinalbin A were, for the first time, also shown to possess an AhR agonistic activity, whereas genistein was not active in this assay. In addition, it was possible to deduce structure-activity relationships. CONCLUSIONS: These results suggest that the identified compounds are the major active principles responsible for the estrogenic and AhR agonistic activities of the crude methanol extract of the aerial parts of Eriosema laurentii.